M31 Safety of combined pirfenidone and nintedanib in patients with idiopathic pulmonary fibrosis. (15th November 2017) - Flaherty, KR; Fell, CD; Huggins, JT; Nunes, H; Sussman, R; Valenzuela, C; Petzinger, U; Stauffer, JL; Gilberg, F; Bengus, M; Wijsenbeek, M
Abstract : Background: Safety data on combined pirfenidone and nintedanib use are limited. Methods: A single-arm, open-label study (NCT02598193 ) assessed safety and tolerability of 24 weeks' pirfenidone (1602–2403 mg/day) and nintedanib (200–300 mg/day) in patients with idiopathic pulmonary fibrosis (IPF) with forced vital capacity (FVC) ≥50% and diffusing capacity of the lung for carbon monoxide (DLco) ≥30%. Before initiating nintedanib, patients had received pirfenidone for ≥16 weeks and tolerated a stable dose of ≥1602 mg/day pirfenidone for ≥28 days. Investigators recorded treatment-emergent adverse events (TEAEs), attributing them to pirfenidone, nintedanib, both or neither. Change from baseline FVC, DLco and King's Brief Interstitial Lung Disease (K-BILD) score were assessed at 24 weeks. The study is monitored by a data monitoring committee. Results: Eighty-nine patients were enrolled. A pre-specified interim analysis was conducted once 63 patients (mean age 68.7 years, 85.7% male) completed (n=50) or discontinued (n=13) 24 weeks' combination treatment. Fifty patients had 330 treatment-related TEAEs (Table); 11 patients discontinued due to TEAEs. Two patients had serious treatment-related TEAEs (Table) but none led to death. Final Results for all 89 patients, including change from baseline FVC, DLco and K-BILD score, will be presented at BTS. Conclusions: Combined pirfenidone and nintedanib use for 24 weeks did not reveal a different safety profile to that expected for either treatment alone. Patients had tolerated a stable dose of pirfenidone before initiation of nintedanib, which may explain why investigators attributed more TEAEs to nintedanib than pirfenidone. Funding: F. Hoffmann-La Roche, Ltd./Genentech, Inc.